Caracterização bioquímica e funcional de uma metaloprotease isolada da peçonha da serpente Bothrops moojeni - Mamede, Carla Cristine Neves (2011)
CHAPTER II: Bothrops snake venoms contain proteins that contribute to the local and systemic effects seen after envenoming, such as edema, myonecrosis, coagulation disorders and hemorrhage. These effects can be triggered by the toxic action of metalloproteinases present in the bothropic venom. This study aimed to perform the purification, biochemical and functional characterization of a metalloproteinase called Moozincin, from Bothrops moojeni snake venom. Moozincin has approximate molecular mass of 28 kDa, displays relevant fibrinogenolytic activity and can be classified as a non-hemorrhagic fibrinogenolytic metalloprotease, in the class P-I. Moozincin was also able to induce edema, myonecrosis and hyperalgesia in experimental animals. Morphological analysis of the evolution of muscle injury revealed the occurrence of degenerative events and leukocyte infiltration already at three hours after application of Moozincin. These effects dominate until 48 hours after administration of the metalloprotease, when hemorrhagic effect was also demonstrated later in skeletal muscle, probably triggered by the action characteristic of metalloproteinases on vascular components and / or indirect action resulting from muscle injury.